2011
DOI: 10.1007/s11434-011-4623-8
|View full text |Cite
|
Sign up to set email alerts
|

An atomic force microscopy study of coal nanopore structure

Abstract: Coal nanopore structure is an important factor in understanding the storage and migration of absorbed gas in coal. A new method for studying coal nanopore structures is proposed. This idea is based on the nano-level resolution of atomic force microscopy, which can be employed to observe the structural features of coal nanopores clearly, conduct quantitative three-dimensional measurements and obtain structural parameters. Analysis results show that coal nanopores are mainly metamorphic pores and intermolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Thus, traditional methods do little to connectivity analyses of pores in coal. Recently, new techniques such as Focused Ion Beam-Scanning Electron Microscopy (FIB-SEM) and X-ray Computed Tomography (X-ray CT) have been successfully applied to study the pores in conventional reservoir and gas shale (Clarkson et al, 2013;Radliński et al, 2009;Yao et al, 2011). While X-ray CT has been applied to study the pores in coal seams (Ramandi et al, 2016;Pant et al, 2015;Golab et al, 2013;Yao et al, 2009;), FIB-SEM has not been widely used in coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, traditional methods do little to connectivity analyses of pores in coal. Recently, new techniques such as Focused Ion Beam-Scanning Electron Microscopy (FIB-SEM) and X-ray Computed Tomography (X-ray CT) have been successfully applied to study the pores in conventional reservoir and gas shale (Clarkson et al, 2013;Radliński et al, 2009;Yao et al, 2011). While X-ray CT has been applied to study the pores in coal seams (Ramandi et al, 2016;Pant et al, 2015;Golab et al, 2013;Yao et al, 2009;), FIB-SEM has not been widely used in coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…The AFM research to date has focused on coal maceral [36,37] or coal surface pore characteristics of surface topography [38]. Here, we use combined multimodal micro-Raman and functional AFM imaging through band excitation-atomic force acoustic microscopy (BE-AFAM) to resolve chemical, mechanical and structural components of coal on the micron-nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that pore volume and frequency are controlled by rank [37]. The average pore size of low-rank coals is larger than that of high-rank coals [39]. A report by Rodrigues and Lemos de Sousa (2002) indicated that high-volatile bituminous A and higher rank coals are dominated by micropores.…”
Section: Pores In Coalmentioning
confidence: 98%
“…In terms of the relationship between porosity and the maceral composition, the research results conducted by different researchers are not consistent due to the difference of the studied samples, the different measuring methods and sometimes even the different coal size classification standards. For example, Mastalerz (2008) reported that vitrinite maceral predominantly contains micropores and inertinite mostly contains mesopores and macropores [39,40]. But Harris and Yust (1976) reported that vitrinite is mainly composed of micropores and mesopores, inertinite of mesopores, and liptinite of macropores.…”
Section: Pores In Coalmentioning
confidence: 99%
See 1 more Smart Citation